Avaliação teórica de um mecanismo passivo de controle de arrasto abordando o ruído aerodinâmico aplicado ao corpo de Ahmed com traseira quadrada - Matheus Quintino Palhares (2019)
A passive drag control device can increase the energy efficiency of automobiles. But, the change in the vehicle design especially in its afterbody shape can alter the noise source related to the turbulent flow over it. It is well-known that the automotive wind noise becomes relevant at a velocity range above 100 km/h and is characterized mainly by dipole sources. Thus, the aim of this study is to simulate the Ahmed’s squared-back model at the industrial scale, at a Reynolds number of 2.26 x 106, and investigate the aerodynamics and aeroacoustics effects induced by a specific configuration of short chamfers in horizontal edges of the base. Simulations based on Unsteady Reynolds-Averaged Navier-Stokes and a technique based on Lighthill’s Acoustics Analogy were done. The simulation reproduced the mean organization of the flow at the near wake to the original model and identified spectral activity of the recirculation bubble with between 0.11 and 0.14. The mean drag coefficient of the model was equal to 0.266 and overestimated by 5.7% the reference experiment data. While considering just the vehicle’s base as a noise generator and a microphone positioned 10 meters apart, a sound pressure level (SPL) up to 124 dB (A) was calculated. The use of chamfers in the model’s base reduced the length and cross section area of the recirculation bubble. Changes in the wake’s spectral activity and the appearance of longitudinal vortices originated at the lateral edges of the chamfers were observed as well. The modified model experienced a drag coefficient reduction in the order of 2.7% compared to the original model. Regarding the aerodynamic noise, the simulation results based on model with drag reduction device revealed a reduction of SPL up to 9 dB (A) at 1/3- octave band centered in 2500 Hz; reduction in the SPL in the spectrum region below 100 Hz; and an elevation of SPL of 8 dB (A) at the band centered in 500 Hz.